Street Vendors (PKL) as the Survival Strategy of Poor Community - Handoyo, Eko; Setiawan, Avi Budi (Universitas Negeri Semarang, 2018)
Street vendors are some of informal sector business actors who are directly related to city government policy. Illegal street vendors as one type of street vendors often get ill-treatment from the city government. It is because in running the business, street vendors occupy public space, such as sidewalks and shoulders, so they are disciplined. Through this phenomena, this study aimed to analyze (1) survival strategy done by street vendors and (2) reasons by street vendors in using public space as a place to trade. Those objectives were further described by employing qualitative descriptive method with data collection technique through interviews and observations. Once the data have been collected, they were analyzed qualitatively interactively. From the research results, it can be concluded. First, being a street vendor for low-level society is the only option and is the most viable way to sustain their lives. Some street vendors do survival strategy in order to meet the needs of everyday life. Second, street vendors use public spaces such as roadsides and sidewalks because (1) there are limitations which make them impossible to occupy locations with obligations to pay, (2) roads and sidewalks are strategic places to peddle merchandise; and (3) lack of attention from government to the needs and welfare of street vendors.